Transition Metal Complexes of Mixed Bioligands: Synthesis, Characterization, DFT Modeling, and Applications - Mohamed S. A. Abdel-Mottaleb; Eman H. Ismail (Journal of Chemistry)
Divalent transition metal complexes [MGlu-Arg (H2O)]H2O and [MGlu-Arg (H2O)]H2O, where M = Co, Ni, Cu, and Zn, Glu = glutamic acid, and Arg = L-arginine, are prepared and characterized using different techniques. DFT and TD-DFT modelling validated and interpreted some experimental results. Weight loss technique reveals efficient corrosion inhibition action of these complexes towards aluminum metal at different temperatures. Our results point to corrosion inhibition through chemical adsorption on the aluminum surface. Additionally, a facile calcination of Co and Cu complexes at 550°C yields nanosized oxides of Co3O4, CoO, and CuO crystalline phases. The complexes show remarkable biological activities towards pathogenic bacteria and fungi. Moreover, in vitro anticancer activity evaluation of these complexes is achieved against hepatocellular carcinoma (HepG-2). The results are correlated with molecular descriptors such as chemical potential and hardness obtained from the frontier orbitals.